A Case of Sarcoidosis of the Central Nervous System and Orbita - Metin Mercan; Aslı Akyol; Yahya Karaman; Hayrunnisa Bolay (Case Reports in Medicine)
Sarcoidosis is a multisystemic disease characterized by granulomatous inflammation. Lung or lymph node involvement is common. We present a rare case of sarcoidosis that began with orbital involvement, and a month later, due to insufficient treatment, it involved the central nervous system. A 49-year-old female patient began suffering from swelling in her right eye, redness, ptosis, and limited eye movements two months ago. Gadolinium-enhanced orbital magnetic resonance imaging showed thickening of the lacrimal gland and the right medial rectus muscle. After three weeks of local antibiotic and steroid treatments, her symptoms were resolved. One month ago, the patient reported sudden weakness in her right arm and leg. After laboratory tests and imaging studies, the patient was diagnosed with probable neurosarcoidosis using the Zajicek criteria and treated with prednisone (1 mg/kg/day). Although sarcoidosis frequently presents with lung and lymph node involvement, it is rarely accompanied by orbital involvement. Patients with orbital symptoms may receive a late diagnosis and insufficient central nervous system treatment. Involvement of the central nervous system in sarcoidosis leads to high morbidity and mortality rates. Therefore, early diagnosis and treatment are very important.